2021
DOI: 10.1021/acsomega.1c03959
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Promoters (La2O3, CeO2, and ZrO2) on the Catalytic Activity of the Modified Vermiculite-Based Bimetallic NiCu/EXVTM-SiO2 Catalyst in Methane Dry Reforming

Abstract: An X-NiCu/EXVTM-SiO2 (X = La, Ce, and Zr) catalyst was successfully prepared by using modified vermiculite as a support by the impregnation method. This experiment investigated the effects of La2O3, CeO2, and ZrO2 promoters on the activity of the NiCu/EXVTM-SiO2 catalyst. The study found that the addition of three different metal oxides did not improve the activity of the NiCu/EXVTM-SiO2 catalyst. On the contrary, some Ni active sites were covered by the promoter, which reduced the number of active sites, resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
4
0
2
Order By: Relevance
“…In the meantime, they further prepared the bimetallic catalyst Ni-M/EXVTM-SiO 2 (M = Co, Cu, Fe) and confirmed that this Ni-Cu/EXVTM-SiO 2 catalyst displayed the best catalytic activity and stability. This is attributed to the better interaction and dispersion of the active components of the formed bimetallic Ni-Cu alloy, enhancing its ability to break C-H bonds [6]. Lu et al prepared various vermiculites supported on Ni catalysts via a plasma radiation treatment and found that the catalyst had high catalytic activity for CO methanation even at a very small Ni loading of 0.5 wt% [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, they further prepared the bimetallic catalyst Ni-M/EXVTM-SiO 2 (M = Co, Cu, Fe) and confirmed that this Ni-Cu/EXVTM-SiO 2 catalyst displayed the best catalytic activity and stability. This is attributed to the better interaction and dispersion of the active components of the formed bimetallic Ni-Cu alloy, enhancing its ability to break C-H bonds [6]. Lu et al prepared various vermiculites supported on Ni catalysts via a plasma radiation treatment and found that the catalyst had high catalytic activity for CO methanation even at a very small Ni loading of 0.5 wt% [7].…”
Section: Introductionmentioning
confidence: 99%
“…[11] Compared with the traditional thermal expansion method, the microwave-assisted preparation of the catalyst not only shortens the preparation time of the catalyst, but also improves the stability of the catalyst. [12] Therefore, the modified vermiculite technique has gradually entered the horizon of researchers. Several scholars have used acid treatment to prepare vermiculite-based molecular sieve support with two-dimensional microporous nanolayers, which have excellent properties such as large specific surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the small layer spacing of vermiculite molecular sieve, which is not conducive to gas diffusion, some scholars use microwave to obtain expanded vermiculite to prepare catalyst support [11] . Compared with the traditional thermal expansion method, the microwave‐assisted preparation of the catalyst not only shortens the preparation time of the catalyst, but also improves the stability of the catalyst [12] . Therefore, the modified vermiculite technique has gradually entered the horizon of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Sendo assim, uma possibilidade é pensar na utilização do metano de forma a evitar a simples queima como combustível. 3 A conversão de metano em produtos de maior valor agregado (etileno e hidrocarbonetos de maior massa molar) fornece outra via para utilização desse gás. 4 Existem dois desafios no densenvolvimento de catalisadores para essa reação: (i) A ligação C -H é muito estável.…”
Section: Por Que Estudar Nanoclusters De óXidos De Lantânio E Cério?unclassified
“…O comportamento catalítico de óxidos La 2 Ce 2 O 7 , CeO 2 e La 2 O 3 têm sido estudado na literatura, 3 entretando, as propriedades, em regime nano, são pouco compreendidas. Estudos teóricos demonstraram que abaixo da temperatura de transição de fase, a temperatura tem pouca influência na morfologia de nanopartículas, que por sua vez é mais influenciada pela composição.…”
Section: Problemas Em Aberto Na Escala Nanométricaunclassified